2019
DOI: 10.1136/bmjopen-2018-025074
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs, practices and knowledge of community pharmacists regarding complementary and alternative medicine: national cross-sectional study in Lebanon

Abstract: IntroductionPharmacists are uniquely positioned to provide patients with evidence-based information in order to ensure effective and safe use of Complementary and alternative medicine (CAM) products.ObjectiveAssess beliefs, practices and knowledge related to CAM products among community pharmacists in Lebanon.Design, methods and settingUsing stratified random sampling, a nationally representative survey was conducted among community pharmacists in Lebanon. Through face-to-face interviews, pharmacists completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 56 publications
7
46
1
Order By: Relevance
“…This is similar to the findings of a study in Trinidad and Tobago, where 84% of doctors and 83% of pharmacists indicated that HCPs should receive more formal teaching about CAM [19]. The researchers in Lebanon, found that most pharmacists requested that continuing education programmes on CAM, be made compulsory to ensure the safe and efficacious use of herbal medicines [22].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This is similar to the findings of a study in Trinidad and Tobago, where 84% of doctors and 83% of pharmacists indicated that HCPs should receive more formal teaching about CAM [19]. The researchers in Lebanon, found that most pharmacists requested that continuing education programmes on CAM, be made compulsory to ensure the safe and efficacious use of herbal medicines [22].…”
Section: Discussionsupporting
confidence: 80%
“…There was a lack of knowledge noted for the side effects, contraindications, and drug interactions for most of the bush/herbs. Similar findings were encountered for pharmacists in Palestine [21] where more than half of the participants did not know side effects, contraindications and herbaldrug interactions; and in Lebanon, where although pharmacists knew about the uses of products such as echinacea and ginkgo biloba, their knowledge of the side effects and drug interactions was poor [22]. Clement et al, also reported similar results for the physicians in Trinidad [15].…”
Section: Discussionsupporting
confidence: 66%
“…In addition, the study showed a deficit in information among HCPs regarding herb-drug interactions. Knowledge deficiencies found in this study were also reported by many studies in the Arab region, including Saudi Arabia, Jordan, Oman, Kuwait, Qatar and Lebanon, as well as in the United States [26,28,29]. A possible reason for HCP's missing answers is because participants were hesitant to answer them, as they did not know the correct answers [28][29][30].…”
Section: Resultssupporting
confidence: 65%
“…The last few decades have been characterized by increased recognition of the role that community pharmacists play in patient care [1] . A study by Quasim and Bayunus [2] revealed that community pharmacists received visits from patients 35 times a year compared to the four times a year a primary care physician was visited.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Quasim and Bayunus [2] revealed that community pharmacists received visits from patients 35 times a year compared to the four times a year a primary care physician was visited. While the general medical practitioners have traditionally been recognized as the gatekeepers of primary care, studies show that community pharmacists receive an estimated 12 to 15 consultations each year [1] . Community pharmacists are strategically positioned to play a central role in care delivery; moreover, Kayyali [3] pointed out that community pharmacists are the largest and most accessible healthcare professional since they are located at the frontline of care delivery.…”
Section: Introductionmentioning
confidence: 99%